Surgical procedures and plasma exchange for ovarian teratoma-associated anti-N-methyl D-aspartate receptor encephalitis: a case report and review of literature - Hu, Yue; Zhang, Jianyuan; Zhang, Peihai; Sun, Baozhi; Zou, Hongli; Cheng, Lei (Frontiers in Oncology, 2023)
We reported a case of ovarian teratoma-associated Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis with recurrent epileptic seizures and disturbance of consciousness. Although surgical excision of the tumor remains the established standard of care, unlike other reported cases, the patient exhibited limited response to early oophorocystectomy, as well as IVIG and steroid therapy; however, a favorable response was observed with Plasma exchange (PE) initiated on postoperative day 12. Literature review revealed no definite recommended surgical extent for ovarian teratomas, and outstanding improvement in patients with anti-NMDAR encephalitis following PE. Our case raises the question regarding the optimal surgical extent for tumor resection, necessitating careful consideration when deciding between oophorectomy and adnexectomy as the preferred surgical procedure for anti-NMDAR encephalitis in female teens and adults. Furthermore, for refractory patients who fail to respond following tumor resection, PE can be performed early instead of immediately initiating second-line therapy.